2022
DOI: 10.3389/fpsyg.2022.916079
|View full text |Cite
|
Sign up to set email alerts
|

English as a Foreign Language Teachers’ Work Engagement, Burnout, and Their Professional Identity

Abstract: Teacher-related variables have been considered as determining factors in shaping educational system. Teacher professional identity is also very important construct that affect teachers’ teaching practice Moreover, the positive and negative emotions are considered sporadically in Chinese English as a Foreign Language (EFL) educational contexts; however, and there is a paucity of research in investigating the relationship between work engagement as a positive emotion and teacher burnout as a negative workrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
1
14
1
2
Order By: Relevance
“…Furthermore, this study has demonstrated a good correlation between career identity, quality of work life, and work engagement. This is consistent with the findings of other scholars ( Remegio et al, 2021 ; Caricati et al, 2022 ; Xing, 2022 ). According to the social identity theory, an individual’s identity can influence their thinking, emotions, and conduct ( Cao et al, 2016 ).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, this study has demonstrated a good correlation between career identity, quality of work life, and work engagement. This is consistent with the findings of other scholars ( Remegio et al, 2021 ; Caricati et al, 2022 ; Xing, 2022 ). According to the social identity theory, an individual’s identity can influence their thinking, emotions, and conduct ( Cao et al, 2016 ).…”
Section: Discussionsupporting
confidence: 94%
“…It holds promising implications, including increased positive emotions, greater involvement and commitment, and improved job performance ( Bakker and Demerouti, 2008 ). In the context of language learning and teaching, EFL teachers’ work engagement is vital for fostering communicative and social involvement, impacting both teachers’ fulfillment, growth, and performance, as well as students’ active participation, academic achievement, and motivation ( Han and Wang, 2021 ; Derakhshan et al, 2022 ; Xing, 2022 ; Li et al, 2023 ; Nazari et al, 2023 ; Zhang et al, 2023b ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Work engagement plays a vital role in shaping EFL teachers’ professional experiences, influencing their motivation, well-being, and effectiveness within the classroom ( Xing, 2022 ). Numerous studies have delved into the factors that impact EFL teacher work engagement, shedding light on various teacher-related variables that contribute to this phenomenon.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Professional identity refers to the teachers' positive attitudes and a strong sense of commitment to the profession [35]. It is a dynamic process [28] [36] as it can be expressed in the teachers' willingness to maintain their profession [35], teachers' behaviours including teaching efficiency and happiness in the classroom [28]. The improvement in the level of professional identity may occur before teaching practice such as when the level of professional identity of new teachers is different from that of expert teachers [37], in the teaching environment [38] or after teaching practice [39].…”
Section: Literature Review 21 Professional Identitymentioning
confidence: 99%
“…Because the deep reciprocal relationship between teachers and emotional satisfaction in environment, society, and workplace teaching can from the conceptualisation of teachers' professional identity [27]. Indeed, teachers' professional identity is considered as a critical variable in fostering work engagement, subsequently alongside with emotion influence on their self-efficacy [28]. Besides, teachers often have positive emotions at work may directly lead to a lasting and positive state of work engagement [29].…”
Section: Introductionmentioning
confidence: 99%